2003
DOI: 10.1046/j.1365-2613.2003.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium administration is associated with enhanced hepatic oxidant stress that may be offset by dietary vitamin E in the rat

Abstract: Summary. It has been proposed that aluminium toxicity may be mediated, at least in part, by free radical generation. We have investigated the effects of aluminium lactate administration on indices of hepatic oxidant stress, and the consequences of concomitant dietary vitamin E, in male albino Wistar rats. Aluminium lactate was administered for 4 weeks, by ip injection at 10 mg aluminium/kg body weight. Groups of animals received a chow diet containing 0, 5, 15, or 20 mg vitamin E/g of food. A control group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 38 publications
4
31
0
Order By: Relevance
“…1,21 Experimental animal models and cell culture studies reveal that aluminum affects the expression of SOD, CAT, GSH peroxidase and GSH possibly leading to membrane fragility as a consequence. 25 SOHE treatment decrease the TBARS level and restored the antioxidant levels in Liver, kidney, lungs and heart of aluminum treated animals. Kumaran & Karunnakaran, 2007 reported that, alkaloids have also been reported to strongly inhibit LPO induced in isolated tissues through its antioxidant activity.…”
Section: Discussionmentioning
confidence: 84%
“…1,21 Experimental animal models and cell culture studies reveal that aluminum affects the expression of SOD, CAT, GSH peroxidase and GSH possibly leading to membrane fragility as a consequence. 25 SOHE treatment decrease the TBARS level and restored the antioxidant levels in Liver, kidney, lungs and heart of aluminum treated animals. Kumaran & Karunnakaran, 2007 reported that, alkaloids have also been reported to strongly inhibit LPO induced in isolated tissues through its antioxidant activity.…”
Section: Discussionmentioning
confidence: 84%
“…On the other hand, Abubakar et al (16) ascertained that Al in hepatocytes, even in small quantities, is associated with an increase in reactive oxygen species and lipid peroxidation. Gonzales et al (5) pointed out a hepatocyte dysfunctionin terms of reduced in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…These include vitamins, fatty acids and antibody (Edenharder et al 1999;Rao et al 2001;Yoshida et al 2010;Turkez et al 2012b). Concomitant treatment with the anti-oxidants provided protection against oxidative damage by mutagens in experimental animals (Abubakar et al 2003;Esparza et al 2003;Geyikoglu et al 2005;. To our best knowledge, no investigation on the anti-genotoxicity potential of X. elegans extracts (XEEs) on mitomycin C (MMC)-induced cytotoxicity in human blood cells was reported in the literature.…”
Section: Introductionmentioning
confidence: 99%